Tax exemptions in excise duty in the context of fiscal efficiency - Edyta Sygut (e-Finanse: Financial Internet Quarterly, 2018)
The basic function of taxes is the fiscal function, which consists in collecting revenue by public authorities. The imposition of non-fiscal functions on taxes causes the weakening of their basic function. The purpose of the article is to present tax exemptions, as well as to assess the fiscal consequences of their application in excise duty in Poland in 2012-2016. The Polish excise duty solutions provide for numerous tax exemptions, whereby it should be noted that a significant part are attributable to EU solutions resulting from harmonisation of this tax. In light of the conducted research, it may be concluded that the applied tax exemptions have a significant influence on fiscal efficiency (causing an average revenue decrease of approximately 7% during the examined period).
Keywords: H21; H30; H53; 330; excise duty; tax exemptions; tax expenditures; fiscal efficiency